2016
DOI: 10.1021/acs.energyfuels.6b01752
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Kinetic Analysis of Ethane Pyrolysis at 0.1 and 2.0 MPa

Abstract: Understanding the pyrolysis of ethane over an extended pressure range can help improve the understanding of the pressure dependence of pyrolysis of higher alkanes. For this work, a variable pressure flow reactor was operated at 1073 K at pressures of 0.1 and 2.0 MPa to gain insight into the effect of pressure on the rate of ethane decomposition and formation of the major products and deposit precursors, such as benzene and toluene. Ethane conversion was achieved by sweeping through residence times over a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Ethane (C 2 H 6 ) pyrolysis is a fundamental process in the global chemical industry and energy economy. More than 100 million tons of ethylene (C 2 H 4 ) are produced annually by steam cracking of ethane at temperatures exceeding 1000 K [1, 2] . As a major component of natural gas, ethane is also widely used for energy production, and the pyrolytic initiation of its combustion plays a central role here as well [3–6] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Ethane (C 2 H 6 ) pyrolysis is a fundamental process in the global chemical industry and energy economy. More than 100 million tons of ethylene (C 2 H 4 ) are produced annually by steam cracking of ethane at temperatures exceeding 1000 K [1, 2] . As a major component of natural gas, ethane is also widely used for energy production, and the pyrolytic initiation of its combustion plays a central role here as well [3–6] .…”
Section: Figurementioning
confidence: 99%
“…These growth mechanisms are important sources of carbonaceous species that decrease yields and efficiency in high temperature processes [8, 30] . Moreover, bimolecular reactions of ethyl have been suggested as the cause of the reduced selectivity of ethane cracking at high pressures [1] . Despite the significance of these reactions, they are often modeled using theoretical or estimated rate constants.…”
Section: Figurementioning
confidence: 99%
“…From a fundamental point of view, ethane is an important intermediate in the oxidation and pyrolysis of hydrocarbon fuels. 20,21 Therefore, understanding pressure effects on the relaxation, dissociation, oxidation, and pyrolysis of ethane is fundamental for the hierarchical construction of higher hydrocarbon fuel models. Hence, there is recent experimental motivation to study the oxidation and pyrolysis of ethane at high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…First, ethane is a prototypical system for studying the kinetics and dynamics of hydrocarbon combustion in both theory and experiment. From a fundamental point of view, ethane is an important intermediate in the oxidation and pyrolysis of hydrocarbon fuels. , Therefore, understanding pressure effects on the relaxation, dissociation, oxidation, and pyrolysis of ethane is fundamental for the hierarchical construction of higher hydrocarbon fuel models. Hence, there is recent experimental motivation to study the oxidation and pyrolysis of ethane at high pressure. Pressures ranging from 10 to 987 atm, where argon is normally used to dilute the gas mixtures, have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the temperature for manufacturing carbonaceous materials ranges from 1000 to 4000 K, in the cases of arc discharge, CVD, laser ablation, pyrolysis, , and combustion. , The high temperature contributes to the atomic C formation from initial reactants. Thus, the nucleation and growth mechanisms of carbonaceous materials at high temperature can simply be seen as the self-assembly of atomic C. For this, many kinetic models have been developed to describe the pyrolysis of hydrocarbons. Nevertheless, these models were employed to compare and fit the elementary reactions with experimental observations to determine dominant reactions in the total conversions alone and cannot provide any dynamic detail at the atomic level. Using reactive molecular dynamics (RMD), our recent work indicated that the pyrolysis product of CH 4 is an orderly cavity-like carbonaceous material as a possible precursor of CNTs, while that of acetylene (C 2 H 2 ) is a disorderly C black .…”
Section: Introductionmentioning
confidence: 99%